Techno-economic efficiencies and environmental criteria of Ocean Thermal Energy Conversion closed Rankine cycle using different working fluids - N., Samsuri; Norazlianie, Sazali; Ahmad Shahir, Jamaludin; M. N. M., Razali (IOP Publishing, 2021)
Ocean Thermal Energy Conversion (OTEC) is a foundation for an appealing renewable energy technology owing to its vast and inexhaustible resources of energy, stability, and sustainable output. Development of OTEC power plant is to exploit the energy accumulated in between the top layer of warm surface seawater (heat source), and the cold layer of deep seawater (heat sink). It operates based on Rankine cycle to produce electricity between the source and the sink at the smallest temperature difference of approximately 20 K. OTEC power plant commonly utilized ammonia as working fluid. Nevertheless, ammonia poses potential lethal health risks and hazardous fluid. Hence, the effect of the working fluid types and the subsequent operation conditions may be critical and therefore become the subject of this study. In addition to OTEC power plant's thermodynamic efficiencies study, this research also explores the economic efficiencies in term of capital cost per net power output ($/kW) and environmental criteria of different working fluids including that of ammonia, ammonia-water mixture (0.9), propane, and refrigerants (R22, R32, R134a, R143a, and R410a). The results showed that ammonia-water mixture gave the excellent performance with regard to the characteristics of heat transfer with the best thermodynamic efficiency of 4.04% compared to pure ammonia with 3.21%, propane with 3.09%, followed by refrigerants from 3.03% to 3.13%. Capital cost of using propane was economically efficient with 15730 $/kW compared to ammonia-water mixture at 16201$/kW, refrigerants from 16990 $/kW to 21400 $/kW, and pure ammonia being the costliest at 21700 $/kW. Despite being lower in its thermodynamic efficiency, propane gave the lowest capital cost and had the lowest toxicity in contrast to all other working fluids. Therefore, propane has the potential to be used as a clean and safe working fluid that would further enhance the OTEC technology.